Examining the associations between control (primary and secondary) appraisals and posttraumatic stress disorder symptoms in Malaysian and Australian trauma survivors - Tamsyn Reyneke; Bryan Lee; Haoxiang Li; Shamsul Haque; Siti Zainab Abdullah; Britney Kerr Wen Tan; Belinda Liddell; Laura Jobson (Frontiers in Psychology, 2023)
BackgroundLittle research has considered the influence of culture on control appraisals in the context of posttraumatic stress disorder (PTSD).ObjectivesThis study aimed to investigate whether cultural group moderated the relationship between control (primary and secondary) appraisals and PTSD symptoms in trauma survivors from Western (Australian) and Asian (Malaysian) cultural contexts.MethodsTrauma survivors (107 Australian with European cultural heritage; 121 Malaysian with Malay, Indian or Chinese cultural heritage) completed an online survey assessing PTSD symptoms and appraisals of control.ResultsCultural group moderated the association between primary control and PTSD symptoms; the positive association was significant for the Australian group but not the Malaysian group. While cultural group did not moderate the association between secondary control and PTSD symptoms, there was an indirect pathway between secondary control appraisals and PTSD symptoms through interdependent self-construal for both cultural groups.ConclusionThe findings indicate that cultural group and self-construal influence the associations between different types of control appraisals and PTSD. Further research exploring the role of culture and different appraisal types in PTSD is needed.